2017
DOI: 10.1002/ece3.3519
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in Tertiary relics: The case of eastern‐Mediterranean Abies (Pinaceae)

Abstract: The eastern‐Mediterranean Abies taxa, which include both widely distributed species and taxa with minuscule ranges, represent a good model to study the impacts of range size and fragmentation on the levels of genetic diversity and differentiation. To assess the patterns of genetic diversity and phylogenetic relationships among eastern‐Mediterranean Abies taxa, genetic variation was assessed by eight nuclear microsatellite loci in 52 populations of Abies taxa with a focus on those distributed in Turkey and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 73 publications
3
23
0
Order By: Relevance
“…Comparing our results with those of previous surveys is, thus, complicated. For instance, genetic diversity of our focal species is similar to that reported for various mountain fir species, like Mediterranean A. nordmanniana or A. cilicica (Hrivnák et al, 2017), but no niche projections are available for these taxa. Other studies that do perform diversity-centrality correlations in montane species, including European forest trees (Dauphin et al, 2020) and Mexican annuals (Aguirre-Liguori et al, 2017), have shown that there is a positive and significant correlation between peripherality (i.e.…”
Section: Geographic Patterns Of Neutral Genetic Diversitysupporting
confidence: 61%
“…Comparing our results with those of previous surveys is, thus, complicated. For instance, genetic diversity of our focal species is similar to that reported for various mountain fir species, like Mediterranean A. nordmanniana or A. cilicica (Hrivnák et al, 2017), but no niche projections are available for these taxa. Other studies that do perform diversity-centrality correlations in montane species, including European forest trees (Dauphin et al, 2020) and Mexican annuals (Aguirre-Liguori et al, 2017), have shown that there is a positive and significant correlation between peripherality (i.e.…”
Section: Geographic Patterns Of Neutral Genetic Diversitysupporting
confidence: 61%
“…This may cause by the seed genetic and environmental factors. All phenotypic characteristics of plants emerge as a result of mutual interaction of genetic structure and environmental condition [31,32,33], and it is known that each genetic structure can react differently to the same environmental conditions [34,35,36]. Studies have shown a significant difference in terms of resistance to water stress both between origins of the same species [15] and between the clonal seed gardens establish with cuttings from the same origin [37].…”
Section: A Water Stress Effects On Seed Germinationmentioning
confidence: 99%
“…piceae could be associated with one of the recent mild interglacial periods, MIS 5 (130–70 kya), or MIS 3 (60–27 kya) (Helmens, 2014). During these periods, the geographic ranges of Abies species expanded and they migrated to lower elevations in the Caucasus Mountains (Pakhomov, 2006) and the Balkan Peninsula (Liepelt et al ., 2009), possibly causing different lineages to come in contact with each other in the Mediterranean region, facilitating gene flow (Linares, 2011; Hrivnák et al ., 2017; Balao et al ., 2020). This contact could have allowed a bridge between Abies hosts in the Caucasus Mountains and Europe, thus initiating the European lineage that became Ad.…”
Section: Discussionmentioning
confidence: 99%